Effect of screen time on sleep quality among young adults: An observational cross-sectional study - Anjali Venkat; Mythri G; Anagha Avinash; Yuktha Hadly Devaraju (Asian Journal of Medical Sciences)
Background: Good sleep quality is associated with a wide range of positive outcomes, including better health, reduced daytime sleepiness, enhanced well-being, and improved psychological functioning. Over the past decade, the availability and usage of electronic devices have increased sharply, making them an integral part of young adults’ lives. Blue light radiation emitted from electronic devices is known to suppress the production of melatonin – a hormone essential for sleep initiation – thereby worsening sleep quality.